Cell wall compositional differences between mealy and non-mealy ‘Forelle’ pear (Pyrus communis L.) - Crouch, Elke Monika (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD(Agric) (Horticulture))--University of Stellenbosch, 2011.